Adoption of Cover Crop Interseeding within Sugarbeet in the Red River Valley. Issue 3 (27th May 2021) - Sigdel, Sailesh; Chatterjee, Amitava
Abstract : The Red River Valley of North Dakota and Minnesota is a major sugarbeet production region in the United States. Due to conventional tillage practices, soils have less residue cover after sugarbeet harvest in the fall, and the soil is exposed to wind and water erosion. In the spring, severe damage due to wind blast of soil particles can cause sugarbeet stand loss. Cover crops have the potential to reduce the impacts of soil erosion and improve nutrient use efficiency. Interseeding cover crops before harvest increases the likelihood of cover crop establishment and growth. Earn 1 CEU in Crop Management by reading the article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/953 .